The interplay of actual and perceived physical fitness in children: Effects on motivation and physical activity. (January 2022) - Henning, L.; Dreiskämper, D.; Tietjens, M.
Abstract: From a sport and exercise psychology perspective, both the actual and perceived physical fitness become important for motivation towards physical activity and persistent physical activity in children no later than middle childhood (Stodden et al., 2008). To date, the effects of actual and perceived physical fitness have been investigated from a variable-centered approach (Jekauc et al., 2017). However, within this approach, the accuracy of the perceived physical fitness remains unconsidered. As actual and perceived physical fitness levels can be divergent, especially in children due to greater egocentricity and hence less comparison processes (Harter, 2006), also the accuracy of perceived physical fitness should be considered. In total, 462 children from 3rd and, approximately nine months later, from 4th grade participated in this study ( M age = 8.79 years). Third-grade students were assessed on their actual physical fitness, perceived physical fitness, and physical activity. In fourth grade, students were asked to fill out questionnaires that assess motivational regulations and physical activity. Polynomial regressions with response surface analyses were conducted to analyze main effects and accuracy effects of actual and perceived physical fitness on motivation and physical activity. Analyses revealed that children with higher actual and perceived physical fitness levels show greater autonomous motivation, higher current physical activity levels and higher physical activity levels nine months later. In addition, children who perceive their physical fitness more accurately show more current physical activity. Results indicate that the interplay between actual and perceived physical fitness does not only have an effect on physical activity but also on autonomous motivation, which is a predictor for long-term physical activity. Therefore, intervention should focus on the promotion of actual and perceived physical fitness. In addition, the ability to accurately assess fitness should be promoted in this age group. Highlights: Actual and perceived physical fitness affect autonomous motivation in children. Higher congruent values lead to higher autonomous motivation. Actual and perceived physical fitness affect physical activity levels in children. Accurate assessments are associated with higher current physical activity levels. Under- or overestimation is associated with lower current physical activity levels.